Reintegración sin desmovilización: el caso de las milicias populares de Medellín (2013)
Narratives on peace processes in Colombia do not often include the 1994 negotiations with the so-called “popular militia” in Medellín -- This article analyzes the development and results of this process, revises the explanations of its failure which were produced in that time, and proposes an interpretation that appeals to a more profound institutional structure that gave way to the negotiation of disorder and the privatization of security, thus developing a thesis suggested by María Teresa Uribe